2021
DOI: 10.1098/rsos.210842
|View full text |Cite
|
Sign up to set email alerts
|

Ecological ramifications of adaptation to size-selective mortality

Abstract: Size-selective mortality due to harvesting is a threat to numerous exploited species, but how it affects the ecosystem remains largely unexplored. Here, we used a pond mesocosm experiment to assess how evolutionary responses to opposite size-selective mortality interacted with the environment (fish density and light intensity used as a proxy of resource availability) to modulate fish populations, prey community composition and ecosystem functions. We used medaka ( Oryzias latipes ) prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 50 publications
(83 reference statements)
1
8
0
Order By: Relevance
“…The selection procedure consisted of mimicking either fishing mortality where only small-bodied individuals were allowed to reproduce (small-breeder SB line), or a more natural mortality regime rather favoring the reproduction of large-bodied individuals (large-breeder LB line) (Reneville et al 2020, Le Rouzic et al 2020). As we have previously reported, the LB and SB lines evolved opposite life-history traits and behaviors: small-breeder medaka grew slower, matured earlier and were less efficient foragers than the large-breeder medaka (Diaz Pauli et al 2019, Evangelista et al 2021.…”
Section: Introductionsupporting
confidence: 56%
See 3 more Smart Citations
“…The selection procedure consisted of mimicking either fishing mortality where only small-bodied individuals were allowed to reproduce (small-breeder SB line), or a more natural mortality regime rather favoring the reproduction of large-bodied individuals (large-breeder LB line) (Reneville et al 2020, Le Rouzic et al 2020). As we have previously reported, the LB and SB lines evolved opposite life-history traits and behaviors: small-breeder medaka grew slower, matured earlier and were less efficient foragers than the large-breeder medaka (Diaz Pauli et al 2019, Evangelista et al 2021.…”
Section: Introductionsupporting
confidence: 56%
“…Bacteria from the Aeromonas genus have been shown to be pathogenic for numerous fish species (Tomás 2012, Wang et al 2018). Our previous findings from the same pond experiment did not indicate any difference in survival probability and somatic growth rate among introduced adults of the LB and SB lines (although LB medaka produced more offspring that grew faster), but suggested that adult and juvenile LB medaka foraged more overall (Evangelista et al 2021). They were especially foraging more on benthic prey hidden in the sediments than the SB medaka (Evangelista et al 2021).…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…Culling-based containment might become even more efficient over the long term because, after several generations, selective removal of large-bodied individuals induces an evolutionary change towards smaller body sizes and earlier maturation, which would not only cause crayfish to disperse less, but are also traits generally associated with lower population growth rates (Evangelista et al, 2020(Evangelista et al, , 2021Heino et al, 2015;Hutchings, 2005). Such harvest-induced evolutionary changes are often considered as slowly reversible (Law, 2000), which is desirable from a long-term management perspective.…”
Section: Implications For the Projection And Management Of Geographic...mentioning
confidence: 99%